Expectation of antibiotics amongst owners of dogs and/or cats during non-routine visits to veterinary clinics in Singapore: a cross-sectional study - Aithal, Seema; Guo, Huiling; Teo, Boon Han; Chua, Timothy; Hildon, Zoe Jane-Lara; Chow, Angela (Frontiers in Veterinary Science, 2024)
ObjectivesThe present study aimed to assess the factors associated with pet owners’ expectations for receiving antibiotics for their pet dogs and/or cats and the factors associated with pets (dogs and/or cats) receiving antibiotics during non-routine veterinary clinic consultations in Singapore.MethodsA cross-sectional study was conducted on consenting pet owners who attended 16 veterinary clinics in Singapore, between March and December 2023. An online survey measured participants’ knowledge of antibiotic use, prior antibiotic use experience, expectation for antibiotics and receipt of antibiotics during the last non-routine clinic consultation for their pets. Multivariable logistic regression models were used to determine the factors associated with expectation of antibiotics and receipt of antibiotics.ResultsAmong the 821 pet owners, over one-in-four (27.5%) expected antibiotics. Owners with prior antibiotic use (adjusted OR 5.18, 95%CI 2.85–9.42) and poor knowledge of antibiotic use (adjusted OR 1.69, 95% CI 1.21–2.35) were 5 times and nearly 2 times as likely as owners without prior antibiotic use and those with good knowledge of antibiotic use respectively, to expect antibiotics for their pets. After adjusting for potential confounders, owners who expected antibiotics (adjusted OR 12.09, 95% CI 7.83–18.68) and had prior antibiotic use for their pets (adjusted OR 8.57, 95% CI 4.75–15.47) were more likely to receive antibiotics for their pets.ConclusionFactors which significantly influenced expectation of antibiotics in pet owners included poor knowledge of antibiotic use and prior usage of antibiotics. This highlights the importance of effective communication by veterinarians to mitigate pet owners’ expectations to address inappropriate antibiotic prescribing.